2021
DOI: 10.1021/acs.organomet.1c00287
|View full text |Cite
|
Sign up to set email alerts
|

Bis(tetramethylaluminate) Lanthanide Complexes Supported by Amidinate Ligands with a Pendant Ph2P═X (X = O, S) Group: Application in Isoprene Polymerization

Abstract: A series of bis­(tetramethylaluminate) lanthanide complexes {2-[Ph2PX]­C6H4NC­(tBu)­N­(2,6-Me2C6H3)}­Ln­(AlMe4)2 (X = O, Ln = La (1); X = O, Ln = Nd (2); X = O, Ln = Sm (3); X = S, Ln = La (4); X = S, Ln = Nd (5)) coordinated by tridentate amidinate ligands bearing a hard (PO) or soft (PS) donor group were synthesized in 82, 71, 54, 77, and 69% yields, respectively. An X-ray analysis revealed that complexes 1–5 feature an intramolecular coordination of the Ph2PX group to the metal ion and both AlMe4 fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In a series of recent publications, it was demonstrated that bidentate and tridentate amidinate ligands bearing various pendant donor groups 2-MeOC 6 H 4 , 17 NC 9 H 6 , 18 2-[Ph 2 P(X)]C 6 H 4 (X = O, S, NPh, N(2,6-Me 2 C 6 H 3 )), 19 (N 2 C 3 H 2 )(C 6 H 2 Me 3 -2,4,6) 20 in the side chain, can be successfully employed as a suitable coordination environment for the synthesis of isolable mono, bis(alkyl), tetramethylaluminate and borohydrido complexes of large rare-earth metals. At the same time, a number of these bis(alkyl) complexes make it possible to polymerize isoprene at a high rate and regulate the stereoselectivity of the process depending on the nature of the ligand ( cis -1,4 up to 98.5%, 19 a , b trans -1,4 up to 84.8% 19 b or 3,4 up to 99.3% 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a series of recent publications, it was demonstrated that bidentate and tridentate amidinate ligands bearing various pendant donor groups 2-MeOC 6 H 4 , 17 NC 9 H 6 , 18 2-[Ph 2 P(X)]C 6 H 4 (X = O, S, NPh, N(2,6-Me 2 C 6 H 3 )), 19 (N 2 C 3 H 2 )(C 6 H 2 Me 3 -2,4,6) 20 in the side chain, can be successfully employed as a suitable coordination environment for the synthesis of isolable mono, bis(alkyl), tetramethylaluminate and borohydrido complexes of large rare-earth metals. At the same time, a number of these bis(alkyl) complexes make it possible to polymerize isoprene at a high rate and regulate the stereoselectivity of the process depending on the nature of the ligand ( cis -1,4 up to 98.5%, 19 a , b trans -1,4 up to 84.8% 19 b or 3,4 up to 99.3% 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early transition metal amidinate complexes have been shown to be catalysts (or precatalysts) for a number of chemical reactions. In addition, complexes with all N-containing ligands including those with amidinates have been used as precursors to microelectronic materials such as metal oxides. We reported earlier reactions of M­(NMe 2 ) 5 (M = Nb, Ta) with H 2 O, yielding oxo-bridged cage complexes [M­(μ 3 -O)­(Me 2 N) 3 ] 4 (Scheme ; M = Nb, 1 ; Ta, 2 ) with elimination of HNMe 2 .…”
Section: Introductionmentioning
confidence: 99%